DEVELOPMENT OF MEDICAL CULTURE IN FUTURE DOCTORS BY MEANS OF NEUROLINGUISTIC PROGRAMMING TECHNOLOGIESe (Proceedings of International Educators Conference, 2023)
This article reflects on the development of medical culture in future doctors through the means of neurolinguistic programming technologies of  future doctors studying in medical institutes.